Regulatory anticipation of postmarket safety problems for novel medicines approved by the EMA between 2001 and 2010: a cross‐sectional study. Issue 6 (11th November 2015) - Zeitoun, Jean‐David; Lefèvre, Jérémie H.; Downing, Nicholas S.; Bergeron, Henri; Ross, Joseph S.
Abstract: Purpose: The aim of the study is to describe preapproval safety concerns expressed by the European Medicines Agency (EMA) following regulatory review and to compare those concerns with subsequent issuance of postmarket safety communications. Methods: All novel medicines approved by the EMA through the centralized authorization procedure from 2001 to 2010 were included. Preapproval safety concerns were identified through examination of information related to regulatory review publicly available on the EMA's website. Relevant postmarket safety events were identified through Dear Healthcare Professional Communications (DHPCs), including those resulting in a withdrawal, issued by at least one of four leading national regulators of the European Union. Results: Among the 184 novel medicines included, the EMA had expressed at least one preapproval safety concern for 110 (59.8%) of them. Then, at least one safety communication was issued for 53 (28.8%) medicines within the postmarket period of study, totaling 90 DHPCs and 5 withdrawals. Overall, these 95 DHPCs and withdrawals were pertaining to 66 different clinical safety events. The EMA had expressed a preapproval concern consistent with the postmarket safety event for 22.7% (15 of 66). The rate of issuance of a postmarket safety communication was not statistically different between medicines with or without any preapproval safety concern (31.8% vs. 24%, p = 0.25). Conclusions: Preapproval safety concerns are frequently expressed by the EMA following regulatory review. However, when comparing postmarket safety communications with prior concerns, anticipation was low. Our findings emphasize the need to systematically conduct postmarket studies dedicated to safety evaluation. Copyright © 2015 John Wiley & Sons, Ltd.